Implementation and Problems of Education Based on Gender Equality, Disability, and Social Inclusion at Schools in Indonesia - Evi Muafiah; Susanto Susanto; Idi Warsah; Desi Puspitasari; Ayunda Riska Puspita (International Journal of Sociology of Education)
Inclusive education in Indonesia requires a serious study on the discourses concerning gender equality, disability, and social inclusion. Hence, this study aimed to uncover the implementation of education based on gender equality, disability, and social inclusion at schools in Indonesia. This study also sought to identify the problems faced by teachers in teaching based on gender equality, disability, and social inclusion. By adopting an explanatory mixed-method design, the first objective was attained by implementing a quantitative survey on 315 teachers of elementary and secondary schools in Indonesia. A descriptive qualitative method was further conducted by involving 30 teachers to confirm the foregoing quantitative data. The second objective was attained by conducting a descriptive qualitative study with the involvement of the aforesaid 30 teachers who had been selected purposively. This study found a moderate implementation of gender equality, disability, and social inclusion education. However, teachers at some schools faced problems related to gender stereotypes, non-inclusive curriculum, unsupportive social expectations, lack of knowledge in teaching students with disabilities, limited resources, and difficulties in adapting teaching methods. This study highlights the need to address stereotypes, promote inclusive education for students with disabilities, and combat social injustice and resource limitations for inclusive teaching.